Hallucinogen use and intimate partner violence: Prospective evidence consistent with protective effects among men with histories of problematic substance use. (July 2016) - Walsh, Zach; Hendricks, Peter S; Smith, Stephanie; Kosson, David S; Thiessen, Michelle S; Lucas, Philippe; Swogger, Marc T
Evidence suggests that hallucinogens may have therapeutic potential for addressing a variety of problem behaviors related to the externalizing spectrum of psychopathology, such as substance misuse and criminality. Intimate partner violence (IPV) is a prevalent form of criminal violence that is related to externalizing pathology. However, the association between hallucinogen use and IPV has not been comprehensively examined. In this prospective study, we examined the association between IPV and naturalistic hallucinogen use among 302 inmates at a US county jail. Cox regression analyses indicated that hallucinogen use predicted reduced arrest for IPV independently (β = −0.54, SE= 0.20, χ 2 =7.19, exp( B )=0.58, p< 0.01) and after accounting for covariates (β=−0.48, SE =0.23, χ 2 =4.44, exp( B )=0.62, p <0.05). These results add to a growing literature suggesting distinct therapeutic potential for hallucinogens to assist in the attenuation of problematic behavior.